Node activity based trust and reputation estimation approach for secure and QoS routing in MANET - Raghavendar Raju L; C R K Reddy (Institute of Advanced Engineering and Science, 2019)
Achieving safe and secure communication in MANETs is a key challenge due to its dynamic nature. A number of security studies disclose that reputation management systems are able to be effectual with less overhead. The reputation of a node is calculated by using automated assessment algorithms depend on predefined trust scheme. This paper proposes a Node Activity-based Trust and Reputation estimation (NA-TRE) approach for the security and QoS routing in MANET. NA-TRE aims to find trust estimation and reputation of a node. The NA-TRE approach monitors the activity changes, packet forwarding or dropping in a node to find the status of the node. The various activities of a node like Normal State (NS), Resource Limitation State (RS) and Malicious State (MS) are monitored. This status of a node is helpful in computing trust and reputation. In this paper NA-TRE approach compared with existing protocols AODV, FACE and TMS to evaluate the efficiency of MANET. The experiment results show that 20% increasing of throughput, 10% decrease of overhead and end to end delay.